Liming and fertilizing on Erexim soil for soybean - Voll, Elemar (2014)
A field experiment was conducted on Erexim soil at Chapecó, Santa Catarina, Brazil, in 1970, to study the effects of liming and fertilizers on soybean (Glycine max (L.) Merril). No significance was registered for nitrogen, or potassium, in soybean yield. Doses of dolomitic calcareous, or P2O5 applied seperately, gave significantly response than when both were applied in combination. The technic critical level of phosphorus in soil was estimated at 10.0 ppm of P, obtained by applying 246 kg/ha as P2O5. This fertilizer P applied in combination with 6.6 t/ha liming correction (1/2 SMP) produced 3,098 kg/ha of soybean. The economic critical level was estimated at 6.4 ppm of P, obtained by applying 116 kg/ha of P2O5, producing 2,750 kg/ha of soybean. The average percentage of the applied phosphorus remaining available in soil after P fertilization was 12.8%, where as for K was 42.2%, measured by the North Caroline method.